Epididymal leiomyoma: a benign intrascrotal tumour. (6th October 2016) - Marcou, M.; Perst, V.; Cacchi, C.; Lehnhardt, M.; Vögeli, T.‐A.
Summary: Physicians will be rarely confronted with epididymal tumours. These represent only 5% of intrascrotal tumours and are mostly (75%) benign. We report the case of a 50‐year‐old white male who was presented with a 5‐year history of a slow‐growing, left scrotal mass, noted through self‐examination. Ultrasound study of the scrotum identified a well‐circumscribed paratesticular mass. On inguinal surgical exploration, a solid, encapsulated, grey‐white mass at the tail of the left epididymis was identified and excised, with intra‐operative pathological consultation showing no signs of malignancy. The diagnosis of an epididymal leiomyoma was determined through subsequent immune‐histopathological analysis. Diagnostic steps preceding operative exploration of a paratesticular, epididymal tumour are briefly analysed and physicians are encouraged to avoid a radical approach, without prior pathological consultation. Epididymal leiomyomas are benign tumours that can be cured through simple, organ‐preserving surgical excision.